Analysis of Students' Mathematical Literacy Skills after Participating in Differentiated Learning with the Outdoor Modeling Mathematics Model - Nida Nur Halimah; Sofnidar Sofnidar; Khairul Anwar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Students’ mathematical literacy remains a persistent challenge across educational levels and continues to be a critical concern in mathematics education. This condition suggests that existing learning practices are largely dominated by conventional instructional approaches that do not adequately accommodate students’ diverse learning needs and readiness levels. The study aimed to analyze the mathematical literacy abilities of Grade VII junior high school students after participating in differentiated outdoor mathematics learning on integer topics. A mixed-methods research design was employed. Quantitative data were collected from 25 students of Grade VII-B at SMP Negeri 17 Batanghari through the implementation of differentiated outdoor learning activities, supported by learning implementation observation sheets. Subsequently, qualitative data were gathered from six selected students to gain deeper insights into their mathematical literacy processes through analysis of test responses and semi-structured interviews. Mathematical literacy was assessed based on students’ performance on literacy-oriented test items and interview data. The results indicated that overall student completion reached 44%, with 20% of students categorized as having high mathematical literacy, 52% moderate literacy, and 28% low literacy. Further analysis based on students’ learning readiness showed that students with high readiness (S1KBT and S2KBT) achieved completion levels of 98.33% and 83.33%, respectively. Students with moderate readiness (S1KBS and S2KBS) attained 81.66% and 80%, while students with low readiness (S1KBR and S2KBR) reached 78.33% and 53.33%. These findings suggest that differentiated outdoor mathematics learning contributes to the development of students’ mathematical literacy across varying levels of learning readiness.